Skull Tutorial for Preclinical Students (Out of Print) - Robert Pope; Mahesh Kamsala; Allison Davis; Jeffrey Altemus; Saritha Reddy; Frank Reilly (Association of American Medical Colleges, 2008)
Abstract This resource is an interactive tutorial serving as an introduction to the skull for first-year medical and dental students. It primarily consists of a series of digitized skull images illustrating bones, foramina, bony landmarks, and protuberances. The objective for creating the courseware was to stimulate more active self-directed learning. The rationale was to integrate skull osteology into a structured format that is readily accessible for local and distance learning and self-assessment. Active learning was achieved by creating 12 tutorial units that target content areas dealing with the different regions and orientations of the skull and mandible. The courseware is user friendly and complements didactic and practical (dissection) activities of beginner health care professionals enrolled in human structure. Since implementation of the courseware in 2001, 8% more students score correct answers on exam questions. Last year, the learners scored at the 77th percentile on the National Board of Medical Examiners anatomy subject examination. Organizing content into discrete tutorials is highly effective in teaching learners a large volume of information without overwhelming them all at once. Exposing preclinical students to the skull tutorial provides them with the essential osteology required for interpretation of standard radiographs and more contemporary imaging techniques such as computed tomography (CT), magnetic resonance imaging (MRI), and positron emission tomography (PET) scans. These observations are supported by recent improvements in learner performance on block and subject shelf exams.